Examining the Makeup of Media Trigger Warnings Online - Zhang, Peixian; He, Yupeng; Haq, Ehsan-Ul; Tyson, Gareth (Proceedings of the International AAAI Conference on Web and Social Media, 2025)
In today’s digital landscape, the prevalence of sensitive online content has made trigger warnings essential. These warnings inform viewers that the content they are about to see contains sensitive artifacts (e.g. violence). This paper studies the use of trigger warnings, exploiting data from two major platforms: Does the Dog Die, a crowdsourcing trigger warnings platform, and IMDb, a media database. We first study how different media types (e.g. films, video games, and TV shows) are labeled with varying trigger warnings and the different co-occurrence patterns among different trigger warnings. We also discover controversy surrounding certain trigger warnings, with inconsistent opinions stated by different people. We further show that different jurisdictions (e.g. USA vs. UK) assign different content ratings (e.g. R-18) for the same media, even when the same trigger warnings are present. Finally, we develop automatic detectors to identify trigger warnings from IMDb text. We achieve F1 scores exceeding 0.7 for all 10 selected trigger warnings.